Goodnight book: sleep consolidation improves word learning via storybooks - Williams, Sophie E.; Horst, Jessica S. (Frontiers in Psychology, 2014)
Reading the same storybooks repeatedly helps preschool children learn words. In addition, sleeping shortly after learning also facilitates memory consolidation and aids learning in older children and adults. The current study explored how sleep promotes word learning in preschool children using a shared storybook reading task. Children were either read the same story repeatedly or different stories and either napped after the stories or remained awake. Children’s word retention were tested 2.5 hours later, 24 hours later and 7 days later. Results demonstrate strong, persistent effects for both repeated readings and sleep consolidation on young children’s word learning. A key finding is that children who read different stories before napping learned words as well as children who had the advantage of hearing the same story. In contrast, children who read different stories and remained awake never caught up to their peers on later word learning tests. Implications for educational practices are discussed.